Video based Swimming Analysis for Fast Feedback - Paavo Nevalainen; Antti Kauhanen; Csaba Raduly-Baka; Mikko-Jussi Laakso; Jukka Heikkonen (My University, 2022)
This paper proposes a digital camera based swimming analysis system for
athletic use with a low budget. The recreational usage is possible during the analysis phase, and no alterations of the pool environment are needed. The  system
is of minimum complexity, has a real-time feedback mode, uses only underwater cameras, is flexible and
can be installed in many types of public swimming pools.
Possibly inaccurate camera placement poses no problem. Both commercially available and tailor made software were utilized for
video signal collection and computational analysis and for providing
a fast visual feedback for swimmers to improve the athletic performance.
The small number of cameras with a narrow overlapping view makes the conventional stereo calibration inaccurate and a direct planar calibration method is proposed in this paper instead. The calibration method is presented and its accuracy is evaluated.
The quick feedback is a key issue in improving the athletic
performance. We have developed two indicators, which are easy
to visualize. The first one is the swimming speed measured from
the video signal by tracking a marker band at the waist of the swimmer,
another one is the rudimentary swimming cycle analysis focusing
to the regularity of the cycle.
Proceedings of the 5th International Conference on Pattern Recognition Applications and Methods (ICPRAM 2016)